Carfilzomib-induced atypical haemolytic uraemic syndrome: a diagnostic challenge and therapeutic success - Darwin, Alicia (BMJ Case Rep, 2021)
Haemolytic uraemic syndrome (HUS) is a thrombotic microangiopathy (TMA) that presents with renal insufficiency, thrombocytopaenia and microangiopathic haemolytic anaemia. Typical HUS is associated with Shiga toxin while atypical HUS (aHUS) is due to overactivation of the alternative complement pathway. aHUS has numerous causes, including drugs, with rare reports of carfilzomib, a proteasome inhibitor used in multiple myeloma, as causative agent. Cases vary in presentation, presenting a diagnostic challenge. Historically, TMAs were treated with plasma exchange. aHUS, however, is considered refractory to plasma exchange and best treated with eculizumab, a monoclonal antibody targeting C5, a terminal complement protein. We report a patient with history of multiple myeloma who presented with headaches, elevated blood pressure, petechiae, ecchymosis and haemolytic anaemia. His condition was determined to be carfilzomib-induced aHUS and he was successfully treated with eculizumab. Early detection and treatment of drug-induced aHUS is vital in reducing morbidity and mortality related to the condition.